Regulation of cellular senescence via the FOXO4‐p53 axis. Issue 12 (25th May 2018) - Bourgeois, Benjamin; Madl, Tobias
Abstract : Forkhead box O (FOXO) and p53 proteins are transcription factors that regulate diverse signalling pathways to control cell cycle, apoptosis and metabolism. In the last decade both FOXO and p53 have been identified as key players in aging, and their misregulation is linked to numerous diseases including cancers. However, many of the underlying molecular mechanisms remain mysterious, including regulation of ageing by FOXOs and p53. Several activities appear to be shared between FOXOs and p53, including their central role in the regulation of cellular senescence. In this review, we will focus on the recent advances on the link between FOXOs and p53, with a particular focus on the FOXO4‐p53 axis and the role of FOXO4/p53 in cellular senescence. Moreover, we discuss potential strategies for targeting the FOXO4‐p53 interaction to modulate cellular senescence as a drug target in treatment of aging‐related diseases and morbidity. Abstract :